Molecular mechanisms underlying the participation of Ribonuclease T2 gene into self-incompatibility of Citrus grandis var. Shatianyu Hort - Qin, Xin Min; Zhang, Yu; Liu, Yu Jie; Guo, Dan Ni; Li, Hui Min (Cellular and Molecular Biology, 2018)
The RIB (ribonuclease T2) of Citrus grandis var. Shatianyu Hort involved in self-incompatibility (SI) mechanism was identified by prokaryotic expression. RT-qPCR results showed that the expression level of RIB in self pollinated stigma is significantly higher than that in cross pollinated stigma. A vector for prokaryotic expression of RIB was constructed after codon-optimization, and the recombinant protein was induced and purified. In vitro pollen germination test indicated that the RIB protein markedly inhibited pollen germination and pollen tube growth. The result is helpful for better understanding of the molecular mechanism underlying the SI in C. grandis.